EPAC IS A KEY MEDIATOR OF cAMP-INDUCED CARDIOPROTECTIVE SIGNALLING. (21st November 2014) - Khaliulin, I; Bond, M; Suleiman, MS
Abstract : It has been shown that cyclic AMP (cAMP)-induced protein kinase A (PKA) activation is very important in a variety of cardioprotective protocols including ischaemic and temperature preconditioning. However, it has been recently found that cAMP can also directly activate Epac. Our data show that a cell permeable cAMP analogue 8-Br-cAMP-AM (8-BR), which activates both PKA and Epac, can protect heart against ischaemia/reperfusion injury. The purpose of our study was to determine whether Epac activation is involved in the cAMP-induced cardioprotection. Experiments were carried out on Langendorff-perfused rat heart and on rat heart myoblasts H9C2. Along with 8-Br, the following cAMP analogues and inhibitors were used: an activator of PKA only, 6-Bnz-cAMP-AM (6-Bnz); activators of Epac only, 8-Br-2′-O-Me-cAMP-AM (O-Me) and 8-CPT-2′-O-Me-cAMP-AM (CPT); a PKA inhibitor H-89 and an Epac inhibitor ESI-09. Exposure of the H9C2 cells to these compounds revealed that 10 µM O-Me and 5 µM 8-Br activate Epac to a similar extent whilst ESI-09 completely blocks this effect of 8-Br. Perfusion of hearts with 10 µM 6-Bnz appeared to activate PKA to the same extent as 5 µM 8-Br. Further experiments demonstrated that neither 6-Bnz nor O-Me can produce cardioprotective effect similar to 8-Br. However, both H-89 and ESI-09 completely abolish 8-Br-induced cardioprotection whilst a mixture of 6-Bnz and CPT induced a strong protective effect. These data imply that activation of Epac alone is unable to protect the heart against ischaemia/reperfusion injury but it represents an essential link in cAMP-induced cardioprotection when activated together with PKA.